Remarks on the Orthography of Word rmṯ in the Old Kingdom - El-Sattar, Ibrahim Abd (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
This paper investigates the orthographies of the word rmṯ in the Old Kingdom and the factors impacting them. It is based on a survey of texts that include this word. It aims to identify features of spelling originality and means of dissemination of orthographical forms. The study also urged with its pronunciation, its plurality and singularity, the nature and significance of its determinatives. Finally, the study concluded that there is an obvious orthography-system of this word which could be geographically, and chronology traced.